Thermal mechanism in magneto radiated [(Al2O3-Fe3O4)/blood]hnf over a 3D surface: Applications in Biomedical Engineering - Guedri, Kamel; Adnan,; Raizah, Zehba; Eldin, Elsayed Tag; EL-Shorbagy, M. A.; Abbas, Waseem; Khan, Umar (Frontiers in Chemistry, 2022)
The nanofluids synthesized by hybrid oxide nanoparticles (Al2O3-Fe3O4 of Lamina shape with 16.1576 shape factor) by considering blood as hosting liquid attained much interest of the researcher more specifically in the field of bio-medical engineering. These nanoparticles progressively utilized in the detection of cancer cells in human body, drug delivery and wound healing etc. because of their progressive high thermal stability and corrosion endurance. The interaction of oxide nanoparticles with blood is a potential motive of interest in the present time and extensively applicable in chemotherapy, theranostic and implant etc. Therefore, the research paradigm is structured to examine the interaction of (Al2O3-Fe3O4) with blood under various significant physical constraints like thermal radiation, magnetic field and slip effects. The model successfully developed by exercising the appropriate similarity equations and then the results plotted by employing numerical technique. The investigation of results reveals that used hybrid nanofluids have magnificent thermal capability and can be used positively to cope the problem faced by the world of nanotechnology.